Adaptability of Miscanthus Cultivars for Biomass Production - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2017)
In 2016, miscanthus dry matter production (DM) averaged 8,890 lb DM/a and did not differ between the two cultivars in production at the Mound Valley Unit of the Southeast Agricultural Research Center. Total three-year production for the cultivars was also similar, averaging 35,050 lb/a.
Keywords: energy crop; warm-season perennial